Assessment of outcome of regenerative endodontics for treatment of periapical lesions - Jadhav, Madhura A.; Handa, Aishwarya; Mundhe, Darshana; Gavali, Neelam; Gaikwad, Ashwini Avinash; Hegde, Pauravi (International journal of health sciences, 2022)
Background: Three key elements are essential for performing REPs: stem cells, scaffolds, and activators. The present study was conducted to assess outcome of regenerative endodontics for treatment of periapical lesions. Materials & Methods: 40 patients with mature incisors, canines, or mandibular premolars showing pulp necrosis and apical periodontitis were divided into group I (REP) and conventional root canal treatment (ENDO) group II. Calcium hydroxide medication was used, and the cavity was sealed. 3 weeks later, patients were treated following their assigned protocol of ENDO or REP. Clinical follow-up examinations were performed at 6 months and 12 months. Results: At 6 months, success was seen in 20 teeth in group I and 18 in group II and failure in 2 in group II. At 12 months, success was seen in 20 in each group. The mean height (mm) at 6 months was 2.5 and 2.8 in group I and II, at 12 months was 1.6 and 1.9. Anterior-posterior dimension at 6 months was 2.6 and 2.7 and at 12 months was 1.8 and 2.2. Mesiodistal dimension at 6 months was 3.1 and 2.5 and at 12 months was 1.8 and 2.1 in group I and II respectively.